AB0826 Does Etanercept Influence Tweak Modulation of Inflammation During Psoriatic Arthritis?. (9th June 2015) - Guis, S.; Berbis, P.; Stephan, D.; Balandraud, N.; Lesavre, N.; Bonnet, N.; Desplat-Jego, S.
Abstract : Background: TWEAK (TNF weakly inducer of apoptosis) is a type II-transmembrane protein, member of the TNF ligand superfamily that can be cleaved to function as a soluble cytokine. Depending on target cell type and micro-environmental conditions, TWEAK triggers multiple cellular responses ranging from modulation of inflammation to cell death. Various data support that TWEAK produced by synovial macrophages may contribute to synovitis in human chronic inflammatory arthritis especially in psoriatic arthritis (PsoA). In PsoA, anti-TNF therapy has been successful in agreement with the key role of TNF in the pathogenesis of this disease and the generation by psoriatic patients of neutralizing anti-TNF autoantibodies referred as "beneficial autoimmunity to pro-inflammatory mediators". However, the role of TNF-alpha in the regulation of TWEAK modulation of inflammation during PsoA remains unknown. Objectives: To assess if anti-TNF therapy affects TWEAK modulation of inflammation during PsoA by evaluating if i) levels of serum soluble TWEAK and ii) levels of anti-TWEAK auto-antibodies generated by PsoA patients are influenced by etanercept therapy. Methods: Serum samples from 13 patients with PsoA were collected before and at two time points during etanercept therapy (weeks 12 and 24). Serum samples of 53 healthy blood donors (HBD) were also collected and analyzed. Serum TWEAK concentrations were evaluated with a commercially available ELISA kit and circulating anti-TWEAK auto-antibodies were detected by a homemade-western blot. Disease activity was assessed according to the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI). Results: Patients with PsoA had significantly higher serum levels of TWEAK compared with controls (respective Means (±SEM) were 645 pg/ml (64) and 467 pg/ml (23); (p=0.006)) but serum soluble TWEAK levels were not correlated with BASDAI (Spearman's coefficients <0.003, p>0.05). Our study showed that soluble TWEAK levels were not modulated by etanercept therapy (respective Means (±SEM) were 645 pg/ml (64)(week 0), 605 (94) (week 12) and 744 (97) (week 24) pg/ml; (p>0.23)). Anti-TWEAK autoantibodies were detected in 9/13 (69.2%) PsoA patients at inclusion and only in 3/53 (5.7%) HBD (p<0.0001). These circulating antibodies were persistent in PsoA patients and detected at similar levels during etanercept therapy. Conclusions: We showed here for the first time that during PsoA a significant elevation of TWEAK serum levels and a production of circulating anti-TWEAK autoantibodies occurred. Our data indicated that these two parameters were not significantly modified by anti-TNF therapy. Acknowledgements: This work was supported by a grant by Pfizer (Pfizer WS 1797055). We thank Françoise Couranjou for her helpful contribution to this work. Disclosure of Interest: None declared